Real Time IoT-Driven Monitoring System on Wind Energy Harvesting for Support Motorcycle’s Battery Storage - Ali, Kharudin; Darobi, Mohd Zikri Zhafri; Mok Hat, Afidatul Nadia; Abd Rahman, Zulkifli; Rifai, Damhuji; Abd Aziz, M Redhwan; Othman, Wan Zulkarnain; Mohamad, Ahmad Joraimee; Abd Rahman, Zammeri; Mohd Zin, Muhamad Syakir; Siaw Paw, Johnny Koh; Chong Tak, Yaw; et al. (International Journal of Synergy in Engineering and Technology, 2026)
Wind energy, which comes from the kinetic energy of moving air, can be turned into mechanical power or electrical energy. A wind turbine is an important part of any wind energy system, as it converts wind into mechanical power for various uses. Improvements in turbine design, generator technology, and power electronics have increased efficiency, including gearless turbine designs. Motorcycles produce a lot of kinetic energy while moving, but this energy is usually wasted. There is no current system to capture and store this energy for later use. This paper offers a solution by developing a mini DC generator turbine system for motorcycles, combined with real-time IoT monitoring for power usage and turbine speed. A DC motor is installed on the motorcycle to generate electrical energy from wind during motion. The energy is stored in a battery and used when needed and providing a sustainable power source. To make the system efficient and reliable, a real time IoT platform is used to monitor energy generation, battery storage, and system performance. This helps users manage energy use, perform maintenance and avoid system failure. By combining wind energy with IoT system, this project supports eco-friendly transportation and energy efficiency. Results show that when the wind turbine speed increases, the voltage also increases. The system can generate up to 12V when the turbine reaches 36 m/s. For every 1 m/s increase in speed, the voltage increases by 0.33V, with a ratio of 3 m/s : 1 V. The results confirm that wind speed is directly proportional to voltage, and the increase is consistent as speed changes.